2022
DOI: 10.1039/d2nr00950a
|View full text |Cite
|
Sign up to set email alerts
|

Precision therapy through breaking the intracellular redox balance with an MOF-based hydrogel intelligent nanobot for enhancing ferroptosis and activating immunotherapy

Abstract: With the advancement and development of nanomedicine, tumor precision therapy provides technical support for effective accumulation, targeted drug delivery, and reduces toxic side effects. In cancer cells, breaking the redox...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In the presence of GSH, the disulfide links of the MOF broke down, leading to the release of the drug. Zhang et al [ 52 ] fabricated a novel smart MOF‐based complex comprising Chlorin e6 (Ce6) an as anticancer drug. In the acidic tumor environment, highly toxic hydroxyl radicals are generated via Fenton reaction.…”
Section: Drug‐loaded Mofs For Cancer Treatmentmentioning
confidence: 99%
“…In the presence of GSH, the disulfide links of the MOF broke down, leading to the release of the drug. Zhang et al [ 52 ] fabricated a novel smart MOF‐based complex comprising Chlorin e6 (Ce6) an as anticancer drug. In the acidic tumor environment, highly toxic hydroxyl radicals are generated via Fenton reaction.…”
Section: Drug‐loaded Mofs For Cancer Treatmentmentioning
confidence: 99%
“…4i, it was found that the mitochondria gradually shrunk after the incubation with Fe 2 @TDF, which was one of the signs of ferroptosis. 36,43,44 Moreover, it has been reported that the depletion of GSH will cause the inactivation of GPX4, resulting in the acceleration of lipid peroxidation. The western blot assay was also applied to determine the expression of the GPX4 protein under different conditions.…”
Section: In Vitro Cytotoxicity and Ferroptosis Validationmentioning
confidence: 99%
“…In vivo: the tumor inhibition effect of the M@C2G or C2 group was relatively weak, while in stark contrast, the C1@M@C2G group significantly inhibited tumor growth (exact data not shown). FeSe 2 −Ce6/MOF@HA/PEI/CpG@HHPA (FSMH) nanoplatform that enables precise combination strategy effects for CDT, PDT, and immunotherapy 72 (Fig. 6c).…”
Section: T1-tumorbearing Micementioning
confidence: 99%
“…as organic linkers, some studies incorporate the photosensitizers into the highly porous structure of MOF to play effective PDT. Zheng and co-workers fabricated a size controllable and environment-adaptive smart FeSe 2 −Ce6/MOF@HA/PEI/CpG@HHPA (FSMH) nanoplatform that enables precise combination strategy effects for CDT, PDT, and immunotherapy 72 (Fig. 6c).…”
Section: Nmofs For Combination Therapy Of Cdt and Other Therapiesmentioning
confidence: 99%